2020
DOI: 10.5114/pm.2020.97840
|View full text |Cite
|
Sign up to set email alerts
|

Emergency peripartum hysterectomy at Jordan University hospital – a teaching hospital experience

Abstract: Introduction Emergency peripartum hysterectomy (EPH) is a foremost operation and is perpetually implemented in the presence of life intimidating hemorrhage during or immediately after abdominal or vaginal deliveries. The aim of this study was to review cases managed at the Department of Gynecology and Obstetrics at Jordan University Hospital (JUH). Material and methods All women who underwent EPH due to any cause in the period from January 2010, to December 2017 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The mean estimated blood loss in this study was 2200 mL, ranging from 500 to 5500 mL. The same results were reported in one study where the mean blood loss was 2210 mL and the mean transfusion was 4 blood units [23]. However, other studies have reported a median estimated blood loss ranging from 2.5 to 7.8 L [24,25].…”
Section: Discussionsupporting
confidence: 87%
“…The mean estimated blood loss in this study was 2200 mL, ranging from 500 to 5500 mL. The same results were reported in one study where the mean blood loss was 2210 mL and the mean transfusion was 4 blood units [23]. However, other studies have reported a median estimated blood loss ranging from 2.5 to 7.8 L [24,25].…”
Section: Discussionsupporting
confidence: 87%
“… 11 Researchers at Jordan University Hospital also found emergency peripartum hysterectomy to be more common following cesarean compared to vaginal delivery. 16 These results reflect the 20-fold increased risk of infection with cesarean compared to vaginal delivery. 17 Of note, the rate of cesarean delivery in our cohort far exceeds the cesarean delivery rate in sub-Saharan Africa, which is just 5%, compared to 27.2% in high resource countries.…”
Section: Discussionmentioning
confidence: 91%
“…Seventy-six percent of our cohort delivered via cesarean. 16 Similarly, the study in Rwanda found that 81% of patients who underwent laparotomy secondary to peripartum infection delivered via cesarean. 11 Researchers at Jordan University Hospital also found emergency peripartum hysterectomy to be more common following cesarean compared to vaginal delivery.…”
Section: Discussionmentioning
confidence: 97%
“…Qatawneh et al . reviewed cases managed by emergency peripartum hysterectomy (EPH) and found that the estimated blood loss during EPH was 2210 mL, 17.6% of their studied women bled > 3000 cc, and the average number of blood units transfused was 3.93 ± 3.43 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%